Multifunctional biomimetic nanoparticles loading baicalin for polarizing tumor-associated macrophages. Issue 42 (17th October 2019) - Han, Shulan; Wang, Wenjie; Wang, Shengfang; Wang, Shuo; Ju, Ruijun; Pan, Zihao; Yang, Tingyuan; Zhang, Guifeng; Wang, Huimei; Wang, Lianyan
Abstract : Immunosuppression and immune tolerance lead tumor cells to evade immune system surveillance and weaken drug efficacy. Abstract : Immunosuppression and immune tolerance lead tumor cells to evade immune system surveillance and weaken drug efficacy. The presence of various immunosuppressive cells in the tumor microenvironment, especially tumor-associated macrophages (TAMs), has been shown to be a driving force in tumor initiation and development. Reversion of the TAM phenotype is an effective way to induce a subsequent antitumor immune response. In this study, we developed baicalin-loaded poly(d, l -lactide- co -glycolide) (PLGA) nanoparticles containing an antigenic peptide (Hgp 10025–33, Hgp) and a toll-like receptor 9 agonist (CpG). The nanoparticles were further coated with a galactose-inserted erythrocyte membrane, which actively targeted the TAMs. The TAM polarization and tumor treatment effectiveness of the nanoparticles were evaluated. The biomimetic nanoparticles showed enhanced cell uptake in vitro and targeted effects in vivo . In addition, compared with baicalin-loaded PLGA-NPs (B@NPs), the biomimetic nanoparticles, such as Hgp/B@NPs-CpG and NPs@RBC-Gala, significantly polarized the TAMs such that they changed from the M2 type to the M1 type both in vitro and in vivo . Subsequently, the infiltration of CD4 + T and CD8 + T cells into tumor sites after being induced by the biomimetic nanoparticles was greatly increased, which suggested a significant enhancement of the immune activation effect and T cell response. In addition, the activation of the T cells and induction of the CTL responses effectively suppressed melanoma tumor growth in vivo . In conclusion, the biomimetic nanoparticles effectively reversed the TAM phenotype from M2 to M1, which further improved the tumor immune microenvironment and promoted tumor immunotherapy. These results suggested that the TAM-targeted biomimetic drug delivery system had the potential to reverse the phenotypes of TAMs contributing to reverse the immunosuppressive tumor microenvironment and promote tumor treatment.